Targeting IL-6 receptor in the treatment of neuromyelitis optica spectrum: a review of emerging treatment options. (3rd May 2020) - Rosso, Mattia; Saxena, Shrishti; Chitnis, Tanuja
ABSTRACT: Introduction : Recent research has shown that IL-6 receptor (IL-6 R) inhibitors like tocilizumab and satralizumab are effective in reducing the relapse rate in patients with NMOSD. Areas covered : This review article explores current concepts in NMOSD management and focuses on IL-6 R as a therapeutic target. The authors delve into the biological and immunological role of IL-6 in the pathogenesis of NMOSD. Further, the authors summarize the most recent findings on the use of anti-IL-6 R monoclonal antibodies, tocilizumab and satralizumab, in the treatment of NMOSD. Expert opinion : A better understanding of the role of cytokines in NMOSD may provide the neurologist with novel therapies for this disease. IL-6 R appears to be a central hub to NMOSD pathogenesis and a relevant therapeutic target.